Hegemonic discourse and sources of legitimacy in Cuba: comparing Mariel (1980) and the Maleconazo (1994) - Port, Lukas (2012)
This research project investigates the sources of legitimacy in hegemonic Cuban discourse, understood to have supported the stability of the Cuban system during crises and challenging times, such as the end of the Cold War and the 1990s Special Period. Evidence was drawn from the Cuban press, namely Granma, Bohemia and Verde Olivo, in two critical periods: the 1980 Mariel episode and the 1994 Maleconazo disturbances as two examples before and after 1989 in order to compare the sources of legitimacy and identify continuities and shifts. The two periods represent recent examples of instability, which dominated the attention of the whole nation. The evidence is based on textual examination using discourse analysis as the method of investigation. The research is written in the discipline of political history, with elements taken from cultural studies and political communication.